Comparative In Vivo Evaluations of Curcumin and Its Analog Difluorinated Curcumin Against Cisplatin-Induced Nephrotoxicity - Şahin, Kazım; Orhan, Cemal; Tuzcu, Mehmet; Muqbil, Irfana; Şahin, Nurhan; Gencoglu, Hasan; Mohammad, Ramzi M. (Springernature, 2014)
Curcumin, a polyphenol, has pharmacological effects including antioxidant, anti-inflammatory and anti-cancer features. In this study, we have performed comparative in vivo evaluations of CDF (curcumin difluorinated) and curcumin in cisplatin-induced nephrotoxicity in rats. Male Wistar rats were divided into four groups: (1) Control; (2) Cisplatin (7 mg/kg body wt, intraperitoneal as a single dose); (3) Cisplatin and CDF (50 mg/rat/day; for 12 days); (4) Cisplatin and curcumin (50 mg/rat/day), for 12 days). Cisplatin treated rats exhibited kidney injury manifested by increased serum N-urea and creatinine (P < 0.001). Kidney from cisplatin treated rats also exhibited significant increase in malondialdehyde (MDA) and 8-isoprostane levels (P < 0.001). Treatment with CDF and curcumin prevented the rise in serum N-urea, creatinine, MDA and 8-isoprostane as compared to experimental control group in kidney (P < 0.05). Compared to curcumin, CDF had greater potential in suppressing cisplatin-induced pro-inflammatory factors NF-kappa B and COX-2 as well as downstream markers Nrf2 and HO-1 (P < 0.05) in kidney. The analysis on anion transport markers (OAT1 and OAT3) showed a similar trend (CDF > curcumin). CDF could reduce the expression of multi-drug resistance markers OCT1, OCT2, MRP2 and MRP4 to a much greater extent than curcumin (P < 0.05). We also demonstrate that CDF influenced the expression of p-mTOR, p-p70S6K1, p-4E-BP1 and p-Akt. These data suggest that CDF can potentially be used to reduce the chemotherapy induced nephrotoxicity thereby enhancing the therapeutic window of cisplatin. The results also proved that compared to curcumin, CDF has superior protective effect in nephrotoxicity.
Keywords: Curcumin; CDF; Cisplatin; Nephrotoxicity